Maya Angelou : a glorious celebration - Gillespie, Marcia (Doubleday, 2008)
An unusual and irresistible look at Maya Angelou's life as well as her myriad interests and accomplishments by the people who know her best--her longtime friends Marcia Ann Gillespie and Richard Long, and her niece Rosa Johnson Butler. Features over 150 sepia portraits, family photographs, and letters.